Citizenship Education Study of the Position of Adopted Children in Customary Law - Pattresya Mailopuw; Fricean Tutuarima; Aisa Abas (CV. Rayyan Dwi Bharata, 2023)
This research is a qualitative descriptive study that aims to find out the implementation of child adoption under customary law in Tananahu District, Teluk Elpaputih District, to find out an overview of citizenship education regarding the rights of adopted children from the perspective of customary law in Neegeri Tananahu, and to find out the process of distributing inheritance to adopted children. based on customary law in Negeri Tananahu. Primary data collection was carried out through interviews with a number of informants who were considered to be directly involved. Data collection techniques used are observation, interviews and documentation. The results of these interviews can show that based on a study of citizenship education in customary law in Tananahu Country regarding the position of adopted children that children who are adopted either from the family or not from the family will become part of the adoptive parent's family. The adopted child will be cared for and all the fulfillment of the child's needs will be borne by the adoptive parents. Before becoming part of the adoptive parent's family, of course, they have gone through the stages and processes according to custom, so that the child who is legally adopted becomes part of the adopting family. Adopted children have the same rights as biological children, such as the right to love, the right to education, and the right to a decent life. According to customary law in Tananahu, the inheritance rights of adopted children and biological children are not the same, but that does not mean that adopted children do not receive inheritance, only with different amounts. Biological children will get more inheritance rights than adopted children.